PENGISIAN KEKOSONGAN JABATAN GUBERNUR (STUDI JABATAN GUBERNUR DI DKI JAKARTA) - Mahropiono Mahropiono (Program Magister Hukum Universitas Lambung Mangkurat, 2016)
The purpose of this thesis is to determine and to assess the mechanism of the turnover and / or charging Jakarta governor according to the Law of the Republic of Indonesia Number 29 Year 2007 as well as knowing the turnover the governor of Jakarta with the enactment of the Law of the Republic of Indonesia Number 1 Year 2015. In the writing of this research using normative legal writing with descriptive research . The primary data sources are the Law of the Republic of Indonesia Number 29 Year 2007 , the Law of the Republic of Indonesia Number 23 Year 2014, the Law of the Republic of Indonesia Number 1 Year 2015 and secondary data sources are in the form of books and literature.According to the results of this research shows that , the Law of the Republic of Indonesia Number 29 Year 2007 does not set out clear explanation about the turnover of governorship of DKI Jakarta . It only refers to the legislation act about the Regional Administration and Local Elections. After the enactment of the Law of the Republic of Indonesia Number 1 Year 2015, the turnover and / or succession vacuum of power of Jakarta governor refers to this law , meanwhile as a special legal (lex specialis) that the law of Local Government overrides the law of Local Government which are in general (lex generalis). lex specialis derogat legi generali.